Protocol for an Open Labelled Randomised Comparative Clinical Study to Evaluate Efficacy of Vangashilajatu and Nishaamalaki in the Management of Madhumeha (T2DM) - Dr. Himani Bhardwaj; Dr. Neelam Kumari; Dr. Neha Lamba (International Journal for Research in Applied Science and Engineering Technology, 2026)
Background: Madhumeha, described in Ayurveda under Vataja Prameha, closely resembles Type 2 Diabetes Mellitus (T2DM), a chronic metabolic disorder characterized by persistent hyperglycaemia. Ayurveda advocates various therapeutic approaches including herbal formulations, dietary regulation, lifestyle modifications, and Yoga for its management. Although Vangashilajatu and Nishaamalaki are widely used in the treatment of Madhumeha, comparative clinical evidence regarding their efficacy remains limited. Objective: To evaluate and compare the clinical efficacy and safety of Vangashilajatu and Nishaamalaki in the management of Madhumeha (T2DM). Methods and Design: This prospective, single-centre, open-labelled, randomized comparative clinical trial will include 60 patients aged 25–60 years diagnosed with Madhumeha. Eligible participants will be randomly allocated into two groups. Group A will receive Vangashilajatu, while Group B will receive Nishaamalaki. Both groups will receive appropriate Pathya-Apathya advice and treatment for 28 days. Clinical assessments will be performed on the 7th, 14th, 21st, and 28th day during treatment and on the 42nd and 56th day during post-treatment follow-up. Expected Results: Primary outcomes will include changes in the cardinal signs and symptoms of Madhumeha described in Ayurvedic texts. Secondary outcomes will assess changes in fasting blood sugar, post-prandial blood sugar, HbA1c, and overall quality of life. Conclusion: This study is expected to generate comparative clinical evidence regarding the efficacy of Vangashilajatu and Nishaamalaki in Madhumeha.